Dental bleaching gels do not alter the surface roughness and microhardness of feldspathic porcelain - Danyelle Cambraia Franco de SOUZA; Lisia Aparecida Costa GONÇALVES; Kellen Cristina da Silva GASQUE; Ana Beatriz da Silveira MORETTI; Bruno Franciel DA SILVA; Rafael Tobias MORETTI NETO (Faculdade São Leopoldo Mandic, 2020)
ABSTRACT Objective: To evaluate whether two different bleaching gels affect the microhardness and surface roughness of feldspathic ceramic specimens, in vitro. Methods: A total of 48 feldspathic porcelain IPS In Line (Ivoclar-Vivadent) discs (16/treatment group) were immersed in distilled water (Group I, Untreated control, UN), or treated with the bleaching gels: Opalescence (15% carbamide peroxide; OPA) and Opalescence Xtra Boost (38%hydrogen peroxide; OPAXB), for 1h or 6h daily for 14 days. Surface roughness (Ra) and microhardness (Knoop, or KNP) measurements were made before and after treatment, and data were subjected to statistical analysis by paired Student's t-test (p < 0.05). Results: Treatments using Opalescence and Opalescence Xtra Boost did not altered surface roughness (p=0.6199861) or microhardness (p=0.14286744) of the feldspathic porcelain tested in this study. Conclusion: Bleaching treatments using Opalescence and Opalescence Xtra Boost may be suitable for treatment in patients having ceramic prosthodontic treatment. Conclusion: Bleaching treatments using Opalescence and Opalescence Xtra Boost may be suitable for treatment in patients having ceramic prosthodontic treatment.